2017
DOI: 10.20944/preprints201709.0165.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coffee Consumption and the Risk of Obesity in Korean Women

Abstract: Abstract:The objective of this study was to investigate the relationship between coffee consumption 12 and obesity in Korean women. We included 5,995 women who participated in a health screening 13 examination at the Korean National Cancer Center between 2007 and 2016. Daily coffee 14 consumption was evaluated using the food frequency questionnaire. Obesity was assessed by body 15 mass index (BMI), and abdominal obesity was assessed by waist circumference (WC). A multiple 16 logistic regression model was used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
2
13
1
2
Order By: Relevance
“…A recent study of Taibah university students and employees (18–45 years of age) demonstrated a high level of Arabic coffee consumption and its positive association with obesity (28% overweight and 33% obese), indicating a health warning against its excessive intake [ 32 ]. Our present study supports the above findings [ 26 , 32 ], showing a direct association between coffee consumption and BMI among female students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study of Taibah university students and employees (18–45 years of age) demonstrated a high level of Arabic coffee consumption and its positive association with obesity (28% overweight and 33% obese), indicating a health warning against its excessive intake [ 32 ]. Our present study supports the above findings [ 26 , 32 ], showing a direct association between coffee consumption and BMI among female students.…”
Section: Discussionsupporting
confidence: 93%
“…Coffee contains several biologically active compounds that result in beneficial effects on obesity and other interrelated abnormalities. However, there are studies reporting direct [ 26 ], inverse [ 27 ], and neutral relationships between coffee consumption and obesity [ 28 ]. Variations in coffee composition and consumption pattern (such as coffee type and amount of intake) are major factors for the inconsistent effect of coffee on human health.…”
Section: Discussionmentioning
confidence: 99%
“…We found that compared with participants consuming instant coffee-mix ≤1 cup weekly, participants who consumed > 1 cup weekly were more likely to be obese. Similarly, a recent study in Korea reported that high coffee consumption was positively associated with obesity as measured by BMI [9]. Additionally, the instant coffeemix intakes were positively correlated with serum triglyceride level [34].…”
Section: Discussionmentioning
confidence: 78%
“…Thus, when the process of obesity is interrupted, these complications will be terminated. In addition, some dietary behaviors associated with obesity include salt intake and coffee consumption [9]. Related studies have reported an association between urine sodium levels as a proxy for salt intake, increasing BMI and metabolic syndrome [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to quantity of water intake, it has always been a question if intra-meal water intake can affect weight. The association of other types of fluids including sugarsweetened beverages, coffee and tea consumption with obesity has been extensively examined in previous studies [14][15][16]. However, limited data are available on the association between whole-day water intake and intrameal fluids consumption in relation to obesity.…”
Section: Introductionmentioning
confidence: 99%